Presence of P2X1 Purinoceptors in Human Platelets and Megakaryoblastic Cell Lines - Vial, Catherine; Hechier, Béatrice; Léon, Catherine; Cazenave, Jean-Pierre; Gachet, Christian (Thrombosis and Haemostasis, 1997)
Human platelets are thought to possess at least two subtypes of purinoceptor, one of which, coupled to G-proteins, could be the P2Y1 receptor (Léon et al. 1997). However, it has been suggested that the unique rapid calcium influx induced by ADP in platelets could involve P2X1 ionotropic receptors (MacKenzie et al. 1996) and the aim of this study was thus to investigate the presence of P2X purinoceptors in platelets and megakaryoblastic cells. Using PCR experiments, we found P2X1 mRNA to be present in human platelets and megakaryoblastic cell lines. In platelets, the selective P2X1 agonist αβMeATP induced a rise in intracellular calcium only in the presence of external calcium and this effect was antagonized by suramin and PPADS. Repeated addition of aMeATP desensitized the P2X1 purinoceptor but only slightly affected the ADP response, while no calcium response to αβMeATP was observed in megakaryoblastic cells. These results support the existence of functional P2X1 purinoceptors on human platelets and the presence of P2X1 transcripts in megakaryoblastic cell lines.